Cervical and Lumbar Spinal Arthroplasty: Clinical Review - Uschold, T.D.; Fusco, D.; Germain, R.; Tumialan, L.M.; Chang, S.W. (American Journal of Neuroradiology, 2012)
SUMMARY: In contrast to cervical and lumbar fusion procedures, the principal aim of disk arthroplasty is to recapitulate the normal kinematics and biomechanics of the spinal segment affected. Following decompression of the neural elements, disk arthroplasty allows restoration of disk height and maintenance of spinal alignment. Based on clinical observations and biomechanical testing, the anticipated advantage of arthroplasty over standard arthrodesis techniques has been a proposed reduction in the development of symptomatic ALD. In this review of cervical and lumbar disk arthroplasty, we highlight the clinical results and experience with standard fusion techniques, incidence of ALD in the population of patients with surgical fusion, and indications for arthroplasty, as well as the biomechanical and clinical outcomes following arthroplasty. In addition, we introduce the devices currently available and provide a critical appraisal of the clinical evidence regarding arthroplasty procedures. ACDFanterior cervical diskectomy and fusionALDadjacent-level degenerative diseaseAORaxis of rotationBAKBagby and KuslichDDDdegenerative disk diseaseHOheterotopic ossificationNDIneck disability indexODIOswestry Disability IndexRCTrandomized controlled trialROMrange of motionSF-36Short Form 36UHMWPEultrahigh molecular weight polyethyleneVASVisual Analog Scale